1995
DOI: 10.1144/gsl.sp.1995.086.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of pyrrolic nitrogen compounds in petroleum during migration: derivation of migration-related geochemical parameters

Abstract: Analysis of a range of crude oils and source rocks appears to indicate that primary and secondary oil migration has a strong impact on the distribution of pyrrolic nitrogen compounds in reservoired petroleum. The migration effects controlling the composition of pyrrolic nitrogen compounds recognized tentatively in this study include (a) the relative enrichments of alkyl carbazoles to alkylbenzocarbazoles, (b) nitrogen-shielded isomers to nitrogen-exposed isomers, and (c) higher homologues to the lower homologo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 43 publications
3
85
0
4
Order By: Relevance
“…Previously it was reported that immature (~ 0.5% R o ) and mature (~ 0.8% R o ) Lower Keg River carbonates as well as Posidonia Shale samples of different maturity (0.48-1.45% R o ) could be discriminated in this plot (Clegg et al, , 1998b. Furthermore, Li et al (1995) had earlier shown that even stronger variations of the methylcarbazoles occurred in a data set based on a much broader selection of crude oil and source rock samples. It may be concluded that the methylcarbazoles are well suited for the differentiation of Abu Gharadig and Shushan crude oils with respect to geographical origin and variations of facies and depositional environment.…”
Section: Compositions Of Carbazolesmentioning
confidence: 80%
See 4 more Smart Citations
“…Previously it was reported that immature (~ 0.5% R o ) and mature (~ 0.8% R o ) Lower Keg River carbonates as well as Posidonia Shale samples of different maturity (0.48-1.45% R o ) could be discriminated in this plot (Clegg et al, , 1998b. Furthermore, Li et al (1995) had earlier shown that even stronger variations of the methylcarbazoles occurred in a data set based on a much broader selection of crude oil and source rock samples. It may be concluded that the methylcarbazoles are well suited for the differentiation of Abu Gharadig and Shushan crude oils with respect to geographical origin and variations of facies and depositional environment.…”
Section: Compositions Of Carbazolesmentioning
confidence: 80%
“…As for the Shushan oils, 4-methylcarbazole is the most abundant and 3-methylcarbazole is the least abundant methylcarbazole. In the work of Dorbon et al (1984) on crude oils and Li et al (1995) for source rocks, it was reported that 4-methylcarbazole is the most abundant and 1-methylcarbazole is the least abundant methylcarbazole.…”
Section: Compositions Of Carbazolesmentioning
confidence: 99%
See 3 more Smart Citations